Mo(S, O)/(Ce, Mo)(S, O) sulfo-oxide with heterovalent metal states for efficient visible-light-driven hydrogen evolution and pollutant reduction via in-situ generated protons. (5th April 2023) - Abdeta, Adugna Boke; Wu, Qinhan; Kuo, Dong-Hau; Li, Ping; Zhang, Hanya; Huang, Ting; Zhang, Jubin; Mosisa, Mengistu Tadesse; Lin, Jinguo; Chen, Xiaoyun
Abstract: The existence of the heterovalent metal states and S doping into Ce–Mo bimetallic oxide improve the photocatalytic activity by generating oxygen vacancy and narrowing the bandgap for suitable water splitting. Spherical and plate likes heterostructure Mo(S, O)/(Ce, Mo)(S, O) sulfo-oxide catalysts with heterovalent metal states and oxygen vacancy defects were synthesized by co-precipitation method for photocatalytic hydrogen evolution reaction. Catalyst labeled as 1-CeMoOS with more oxygen vacancies and high Ce 3+ /(Ce 3+ +Ce 4+ ) ratio evolved 405.18 μmol/h H2 and achieved AQE of 13.72%, whereas reduced 76.43% 4-NP and 91.52% RhB by in-situ generated protons. S doping, oxygen vacancy creation, Ce and Mo heterovalent states have narrowed the bandgap by substituting oxygen with sulfur, promoted the photogenerated charge carriers' effective separation, and prolonged the lifetime of electrons. The oxygen vacancy formation with a subsequently partial Ce 4+ -to-Ce 3+ conversion achieves CeMoOS catalysts with excellent PHER and provides a promising way to improve photocatalysts' visible light PHER activity. Graphical abstract: Image 1 Highlights: Mo(S, O)/(Ce, Mo)(S, O) sulfo-oxide with Ce 4+ /Ce 3+ and Mo 6+ /Mo 4+ states synthesized. Ce 4+ /Ce 3+ and Mo 6+ /Mo 4+ redox cycle produces surface oxygen vacancy. Introduced S in Mo metallic and Ce–Mo bimetallic oxide narrows the band gap. Ce3 + .→Ce4 + and Mo4 + →Mo6 + electron transport facilitate fast transfer of e − for PHER. PHER mechanism over Mo(S, O)/(Ce, Mo)(S, O) sulfo-oxide proposed and discussed.